ANALISIS PERSEDIAAN BAHAN BAKU KEDELAI PADA INDUSTRI TAHU AFIFAH DI KELURAHAN NUNU KECAMATAN TATANGA KOTA PALU - Mohammad Rizki; Made Antara; Dance Tangkesalu (Agroland: Jurnal Ilmu-ilmu Pertanian, 2013)
Afifah tofu industry is an industry with the largest tofu production capacity in Palu with      a total production of 250 tons per year, but the handling of the raw material has not been optimized yetleading to over stock each month, which in turn can cause over cost. The purposes of this study were to determine the economic purchase of the amount of soybeans raw material, to determine the total economic cost of supply, to determine the amount of safety stock of soy beans raw material, and to determine the reorder point on the Afifah tofu industry in Nunu Village Tatanga Palu. This research was conducted from September to October 2012. The number of respondents was two people such as the manager and an administrator of Afifah Tofu Industry determined by purposive technique. Data collected was primary and secondary data which then analyzed using Economic Order Quantity (EOQ), Total Cost of Inventory, Inventory Safety, and Reorder Point. The economic purchase of soybean raw materials by the Afifah Tofu Industry should be done in July, August and October 2012 with the amount of 72541.63 kg, 59990.31 kg, 60419.41 kg, and 59337.10 kg respectively. The total economic cost of supplies spend during July, August and October 2012 were IDR 1,177,497.35, IDR 929,248.08, IDR 1,024,312.45. and IDR. 1,006,158.04, respectively. Safety stock that should be always ready in the ware house from July to October 2012 was 5434.06 kg. The reorder point that must be made in July, August and October 2012 when the amount of the raw material reached 17134.32 kg, 15109.92 kg, 15503.96 kg, and 15004.56 kg respectively. Key Words : Reorder point, safety stock, soybeans, and tofu.